2021
DOI: 10.3390/geosciences11030116
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Preferences of Visitors in the Bohemian Paradise UNESCO Global Geopark

Abstract: There are some localities in the Bohemian Paradise Geopark that suffer from temporal overtourism in the high season. On the other hand, more than half of the geopark is not so often visited by tourists, although very attractive geosites can be found there too. In the most visited localities, nature is damaged due to overloading of the tourist infrastructure, while elsewhere there is pressure driven by municipalities to increase the number of tourists. For this reason, we organized a large questionnaire survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…Rural tourists are attracted to rural areas in Madeira by quite generic features" (p. 828). In addition, Drápela et al [82] studied the motivation and preferences of visitors in the Bohemian Paradise UNESCO Global Geopark and found that most visitors were not primarily interested in geology. They indicated that many of the visitors preferred to stay in nature without an educational element.…”
Section: Discussionmentioning
confidence: 99%
“…Rural tourists are attracted to rural areas in Madeira by quite generic features" (p. 828). In addition, Drápela et al [82] studied the motivation and preferences of visitors in the Bohemian Paradise UNESCO Global Geopark and found that most visitors were not primarily interested in geology. They indicated that many of the visitors preferred to stay in nature without an educational element.…”
Section: Discussionmentioning
confidence: 99%
“…The map is available at https://zywaplaneta.pl/po-poznaniu/ on the geoeducational website maintained by the author, which is viewed by readers that describe themselves in the communications with the author as teachers, parents of children interested in Earth science, amateur collectors, sport tourists and students. Given that many geotourists come from these groups (Drápela et al 2021 ), the website can be used to measure the geotouristic potential of geodiversity sites. Counts were recorded from March 2021 to August 2021, starting during the COVID-19 lockdown.…”
Section: General Public Preferencesmentioning
confidence: 99%
“…The name of Bohemian Paradise (Český ráj in Czech) is unofficial and was likely introduced in the nineteenth century by visitors to the spa resort of Lázně Sedmihorky, located at the foot of a sandstone rock city of Hruboskalsko (Kubaliková 2016;Drápela et al 2021). Among the most popular places for visitors were the ruins of Trosky castle, where one of the medieval castle towers was converted into a viewing tower.…”
Section: Unesco Global Geopark Bohemian Paradisementioning
confidence: 99%
“…Until now, it is the only Czech geopark in the network of UNESCO Global Geoparks. The geopark covers a much larger area than the Protected Landscape Area, initially more than 700 km 2 , later expanded to 833 km 2 (Drápela et al 2021). However, despite various efforts to popularize different parts of the geopark, whose geoheritage also includes important sites of Palaeozoic volcanism (Migoń and Pijet-Migoń 2020), tourist visitations remain very unevenly distributed in space and strongly concentrated in sandstone rock cities.…”
Section: Unesco Global Geopark Bohemian Paradisementioning
confidence: 99%
See 1 more Smart Citation